FORMULASI SOSIS ANALOG SUMBER PROTEIN BERBASIS TEMPE DAN JAMUR TIRAM SEBAGAI PANGAN FUNGSIONAL KAYA SERAT PANGAN - Ambari, Dewi Pratiwi; Anwar, Faisal; Damayanthi, Evy (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
The purpose of this study was to develop formula of sausage based on tempeh flour with the addition of oyster mushroom (Pleurotus ostreatus) as functional food rich in protein and dietary fiber as healthy snack product for children. Sausage was formulated by addition of oyster mushroom used trial and error method. A selected formula was determined based on semi trained panelist preference. Acceptance of the selected sausage formula was examine by children using hedonic test. The contribution of protein and dietary fiber contained in sausage per serving size (50 g) was calculated for general consumer. The accepted sausage with 20% oyster mushroom addition contained 24% of protein and can be claimed as source of protein and 7.64 g of dietary fiber per 100 g and can be claimed rich in dietary fiber.